Strength Analysis of Kereta Kapsul's Bogie Frame Using Finite Element Method - Alfiando - Nim: 13114136 , Ferdinand
The growth of the number of vehicles each year has increased. Increasing the number of vehicles is directly proportional to the level of congestion that occurs. One solution in solving the problem is to apply public transport such as Kereta Kapsul. To ensure the safe operation of Kereta Kapsul, the design of the Kereta Kapsul must meet the requirements of the standard. This bachelor's report contains an analysis of the strength of bogie frame of Kereta Kapsul based on PM No. 175 Year 2015 and EN 13749 2011. The purpose of this research is to do numerical analysis of Kereta KapsulÃ‚Â’s bogie frame from static load according to EN 13749 and PM 175. The level of structural safety is determined based on standard criteria. Based on the static analysis of the case of loading of exceptional load and normal operational load based on EN 13749 2011 standard, the maximum stress that occurs is 427 MPa for exceptional load case and 282 MPa for the case of normal operational load. The smallest safety factor from all the load cases is 1,23.